A Study on the Employees’ Well-Being and Productivity of Working from Home during Pandemic COVID-19 in Indonesian Telecommunication Industry - Santiawaty, Mira (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Every part of our work and lives has been impacted by the COVID-19 pandemic. Companies, organizations, and institutions encouraged their employees to work remotely from home in response to national and local containment policies. This study analyses the impact of the employees’ job productivity and their ability to balance their work with their personal life during work from home (WFH). Most countries have made WFH a policy priority. The policies must be created with the practicality of both employers and employees in mind. However, the current situation offers a unique perspective on how well working from home may be done. Working from home has an impact on employee productivity, according to the findings of the study. While some of the factors have a positive or negative impact, the impact of others is depending on the employees' characteristics and attitudes, as well as the circumstances they face in their own home. This study uses primary data by gathering questionnaires from Indonesian telecommunication employees especially especially those that focus to manage the Corporate or Business to Business (B2B) segment, in order to understand their perspectives on working from home. The findings are assessed using SPSS Statistics and Partial Least Square (PLS) Smart software based on the 156 questionnaire sets gathered.